Penerapan Kelangsungan Usaha Bagi Debitor Pailit Dalam Penyelesaian Perkara Kepailitan Dan Penundaan Kewajiban Pembayaran Utang - Erwin Simaremare; Merry Tjoanda; Ronald Saija (TATOHI: Jurnal Ilmu Hukum, 2023)
Introduction: The application of the principle of business continuity is very difficult for debtors to apply.Purposes of the Research: The purpose of this research is to examine and find out what are the factors that can affect the implementation of going concern for debtors in bankruptcy and postponement of debt payment obligations and the application of going concern as an effort to fulfill the obligations of bankrupt debtors to creditors in bankruptcy matters. Methods of the Research: The method used in this research is normative juridical research method, analytical descriptive research type, sources of legal materials are primary legal materials, secondary legal materials and tertiary legal materials. Analysis of legal materials and methods of analysis of legal materials.Results of the Research: The results of this research and discussion show that: (1) In the application for bankruptcy and PKPU should not only look at the requirements as in Article 2 paragraph (1) and through simple evidence, but also the importance of an insolvency test to determine the extent of the debtor's ability to carry out his obligations, so that The business continuity of the debtor is also protected from being declared bankrupt immediately. (2.) With the continuation of coal mining operations, the bankrupt debtor PT. Rinjani Kertanegara with the aim of increasing bankruptcy assets, it is likely that the rights of creditors on their receivables will be fulfilled.